Older Adults' Experience Using Patient Portals in Communities: Challenges and Opportunities. Issue 1 (January 2019) - Son, Hyojin; Nahm, Eun-Shim
Abstract : Patient portals can be beneficial for older adults who manage their own health. However, there is a lack of research on older adults' experience using patient portals in the community. The aim of this study was to assess older adults' perceived usability of patient portals they currently use. This was a secondary data analysis using selected baseline data from an online trial that tested the effects of a 3-week Theory-Based Patient Portal eLearning Program, and included 272 older adults recruited online. Data were analyzed using descriptive statistics and content analysis. Most participants owned patient portal accounts (n = 194 [71.3%]). Self-efficacy for using patient portals was relatively low (mean, 27.1; range, 0–40), and perceived usability of patient portals was also low (mean, 28.7; range, 6–42). The most-favored features of patient portals were review of medical information and eMessaging. The main difficulties in using patient portals were associated with login/access and specific portal functions. Managing multiple patient portals was a particular challenge for many participants. Findings from this study indicate the importance of providing proper levels of training and technical support to older adults to maximize use and improve outcomes of patient portal implementation.